2008
DOI: 10.1088/0004-6256/135/5/1946
|View full text |Cite
|
Sign up to set email alerts
|

HD 148937: A MULTIWAVELENGTH STUDY OF THE THIRD GALACTIC MEMBER OF THE Of?p CLASS

Abstract: Three Galactic O-type stars belong to the rare class of Of?p objects: HD 108, HD 191612, and HD 148937. The first two stars show a wealth of phenomena, including strong X-ray emission, light variability, and dramatic periodic spectral variability. We present here the first detailed optical and X-ray study of the third Galactic Of?p star, HD 148937. Spectroscopic monitoring has revealed low-level variability in the Balmer and He ii λ4686 lines, but constancy at He i and C iii λ4650. The Hα line exhibits profile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
108
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(127 citation statements)
references
References 62 publications
(80 reference statements)
17
108
0
2
Order By: Relevance
“…In the past, stars displaying this feature were classified by Walborn (1972) in a separate category, dubbed Of?p. In recent years, this category has attracted a lot of attention, as one can see from the numerous publications (Walborn et al 2003(Walborn et al , 2004Donati et al 2006;Howarth et al 2007;Hubrig et al 2008;Nazé et al 2001Nazé et al , 2004Nazé et al , 2007Nazé et al , 2008a. They dealt with the peculiar properties of these stars (for a summary see Nazé et al 2008b) and led to a modification of the definition of these stars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, stars displaying this feature were classified by Walborn (1972) in a separate category, dubbed Of?p. In recent years, this category has attracted a lot of attention, as one can see from the numerous publications (Walborn et al 2003(Walborn et al , 2004Donati et al 2006;Howarth et al 2007;Hubrig et al 2008;Nazé et al 2001Nazé et al , 2004Nazé et al , 2007Nazé et al , 2008a. They dealt with the peculiar properties of these stars (for a summary see Nazé et al 2008b) and led to a modification of the definition of these stars.…”
Section: Introductionmentioning
confidence: 99%
“…lines weaker than for typical Of supergiants (Nazé et al 2008a;Walborn et al 2010). Stars that appear otherwise normal but display strong C iii λ 4650 emission are now called "Ofc" stars (Walborn et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A previous 3-yrs spectral monitoring revealed small-amplitude (a few percent of the peak's amplitude) variations of the Hα line, with a potential period of 7d (Nazé et al 2008b). While the X-ray data were undistinguishable from those of HD 108 and HD 191612, the optical properties thus appeared quite different from those of the other two "prototypical" Of?p stars (which display large variations of many lines, occurring with a long period and correlated with rather large photometric changes).…”
Section: Hd 148937mentioning
confidence: 85%
“…These objects were then known to display strong C III 4650 emission lines but recent studies showed that this is not their sole peculiar characteristics (in fact, at the present time, stars displaying "only" strong C III 4650 emission should be classified as Ofc, see Walborn et al 2010). Of?p stars also possess: narrow P Cygni/emission features in Balmer, HeI,... lines which vary in a recurrent manner; correlated photometric variations; strong magnetic fields; and large X-ray overluminosities (for a review, see Nazé et al 2008a). Five Galactic Of?p stars are known, but only the first three stars which were identified as such in the 1970s (the so-called "prototypical" objects HD 108, HD 148937, HD 191612) have been extensively studied, though some questions remained open about their physical properties.…”
Section: Introductionmentioning
confidence: 85%
“…Likewise, the peak X-ray luminosity of VFTS 399 is two orders of magnitude greater than that found for Of?p stars and the subset of strongly magnetic O-type stars which, in turn, are X-ray over-luminous with respect to the wider population of massive stars (cf. Nazé et al 2008;Clark et al 2009, and refs. therein).…”
Section: Understanding the X-ray Emissionmentioning
confidence: 99%